ANALISIS KELAYAKAN USAHA SERAT ABAKA DI DESA ESSANG KECAMATAN ESSANG KABUPATEN KEPULAUAN TALAUD - Garuda, Mira; Sendow, Martha Mareyke; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2022)
This study aims to analyze the feasibility of the Fiber Abaka business in Essang Village, Essang District, Talaud Islands Regency. The research was carried out from June to July 2021. The data collected were primary data obtained from observations, interviews and distributing questionnaires (list of questions) to respondents. Secondary data was obtained from the Village Head Office, as well as data related to research via the internet. The data analysis method used in this research is the quantitative descriptive method. The results showed that the Fiber Abaka business had a revenue value of Rp. 12,000,000 per month with a monthly income of Rp. 5,409,347, - and the R/C ratio obtained a value of 1,82. Thus, the Fiber Abaka business in Essang Village, Essang District, Talaud Islands Regency is feasible because the results of the R/C value are > 1.